Identifikasi Soil Transmitted Helminth (STH) Anak Usia 7-10 Tahun Menggunakan Sampel Feses Metode Natif - Nurfadillah; Asriyani Ridwan; Dzikra Arwie (Stikes Panrita Husada Bulukumba, 2021)
The background of this research is that Soil-Transmitted Helminth type worm infection is an infection that can be transmitted through the soil including Ascaris lumbricoides, Trichuris Trichur, and Hookworm. In Indonesia, worm infection is the most common health problem in urban and semi-urban areas that have poor sanitation, personal hygiene, and socioeconomic conditions. Intestinal nematode eggs are happy in areas where the environment is a slum, there is inorganic waste, and One of the locations in the Final Disposal Site (TPA). The aim of this research is to determine the type of intestinal nematode worm eggs or Soil-transmitted helminth (STH) in the feces of children aged 7-10 years in the area of the ​​final disposal site in Borong Manempa Hamlet, Polewali Village Bulukumba 2020. This research method uses the native method with the Accidental Sampling technique. The conclusion of this study is that 2 cases of positive samples were found with a percentage of 10% infected with Soil-Transmitted Helminth from the Ascaris lumbricoid group of the 20 samples examined, and 18 samples were negative with Soil-Transmitted Helminth with a percentage of 90%.